Syngas production from microwave plasma gasification of oil palm char - Norasyikin, Ismail (2015)
Gasification is heating-up of solid or liquid carbonaceous material with some gasifying agent to produce gaseous fuel. Conventional gasification normally operates at higher pressure than atmospheric pressure and requires heat up during startup compared to microwave gasification. In this study, both microwave gasification and microwave plasma test rigs were designed to produce syngas from char. A quartz reactor of 600mm length and 20mm internal diameter with swirling gas inlet was designed as the gasification reactor. CO 2 was used as a gasifying agent for syngas production. Oil palm empty fruit bunch (EFB) char and oil palm shell (OPS) char were used as the carbonaceous materials. The flow rate of CO 2 varied from 1 to 4 1pm. The microwave output power was supplied continuously at 800W for 5 mm. The syngas was analysed using gas chromatograph (GC) Agilent 6890 fitted with packed column, Thermal Conductivity Detector (lCD), and capillary column for measuring volumetric concentration of CH4, CO 2, CO, and H2. From the study, it was found that EFB char is better than OPS char as gasification fuel due to high porosity and surface area that will increase the char reactivity towards CO2. For plasma gasification, the temperature increment promoted by the addition of microwave absorber using activated carbon (AC) increased the CO composition. The optimum condition for microwave char gasification of EFB was 3 1pm with 25 wt% AC that produced syngas with 1.23 vol% CH4, 20.88 vol% CO2,43.83 vol% CO, 34.06 voI% H2 and the calorific value of 9.40 MJ/kg. For OPS it was at 2 1pm with 1.12 vol% CH4, 35.11 vol% CO2, 35.42 vol% CO, 28.35 vol% 112 and the calorific value of 7.32 MJfkg. The highest carbon conversion efficiency for EFB and OPS chars were 76.02% and 67.72%, respectively. CO2 flowrates affected the carbon conversion efficiency because it is related to reactivity of different type of char. As EFB char has higher surface area and larger pores than OPS char, the ability to adsorb the gasifying gas is better than OPS, thus resulting in higher carbon conversion. The best gasification efficiency was 72.34% at 3 1pm, 10 wt% AC for EFB with 12% unreacted carbon. For OPS, the maximum gasification efficiency was 69.09% at 2 1pm, 10 wt% AC with 18% unreacted carbon. In conclusion, plasma gasification of oil palm waste is an alternative for solid waste treatment that uses less energy, time, and cost.